2009
DOI: 10.1136/jnnp.2009.182444
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of medical and neurological complications in patients with aneurysmal subarachnoid haemorrhage

Abstract: Treatment of patients with aneurysmal subarachnoid haemorrhage not only involves securing the aneurysm by endovascular coiling or surgical clipping but also prevention and treatment of the medical and neurological complications of the bleed. These acutely ill patients should be looked after in specialised centres by a multidisciplinary team that is available 24 h a day, 7 days a week. No medical intervention is known to improve outcome by reducing the risk of rebleeding but oral nimodipine should be standard c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Again the overall outcome did not appreciably improve in patients treated with tranexamic acid, despite an impressive reduction in rebleeding. If this trial is pooled with the 9 other trials included in the Cochrane review, there is still no effect on overall outcome [110]. Further trials with ultra-early and short-term tranexamic acid should be performed before this therapy can be implemented in clinical practice.…”
Section: Aneurysmal Sah – Ruptured Aneurysm (Ria)mentioning
confidence: 99%
“…Again the overall outcome did not appreciably improve in patients treated with tranexamic acid, despite an impressive reduction in rebleeding. If this trial is pooled with the 9 other trials included in the Cochrane review, there is still no effect on overall outcome [110]. Further trials with ultra-early and short-term tranexamic acid should be performed before this therapy can be implemented in clinical practice.…”
Section: Aneurysmal Sah – Ruptured Aneurysm (Ria)mentioning
confidence: 99%
“…This was previously demonstrated by our group 7 and was thought to be secondary to the higher survival in this population, coupled with the significant number of investigations as well as available therapeutic options for this condition. 34,35 This study demonstrates that total cost among ICU patients with intracranial hemorrhage is driven by factors that commonly influence cost in critically ill populations.…”
Section: Discussionmentioning
confidence: 83%
“…The authors concluded that the cEEG monitoring can provide prognostic information in poor-grade SAH patients. Despite the lack of evidence that cEEG monitoring improves outcome, clinicians often favor using this in SAH patients with depressed mental status to help diagnose non-convulsive seizures and dictate AED initiation [21,35,43,44].…”
Section: Non-convulsive Seizuresmentioning
confidence: 99%